2019
DOI: 10.1159/000490305
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics in Human Milk Research

Abstract: The link between food and health is complex, particularly for the developing neonate, as the period after birth is the time when long-term programming is occurring notably in the neurologic, immune, and metabolic regulatory systems. Breastfeeding is known to have short-and long-term benefits, and yet the intricate relationship of this unique food with the neonate is not fully understood. Application of multi-omic approaches incorporating new bioinformatic tools will allow for better characterization of phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The postnatal period is a critical stage for infant’s physiology, accompanied by rapid changes in brain development, and in metabolic, immunologic, intestinal, and physiological systems [1]. Human milk undergoes dynamic changes in composition during lactation to provide all nutrients and other bioactive substrates for optimal infant growth and development, and exclusive breastfeeding (EBF) is recommended during the first 6 months of life [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The postnatal period is a critical stage for infant’s physiology, accompanied by rapid changes in brain development, and in metabolic, immunologic, intestinal, and physiological systems [1]. Human milk undergoes dynamic changes in composition during lactation to provide all nutrients and other bioactive substrates for optimal infant growth and development, and exclusive breastfeeding (EBF) is recommended during the first 6 months of life [2].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of human milk bioactives on early infant physiology and development are diverse; effects may reach the insulin signaling cascade, the hepatic mitochondrial system, and possibly the mechanistic target of rapamycin (mTOR) signaling pathway, vital to cell growth, protein and lipid synthesis, or lipid and adiposity accumulation and adipogenesis [1,19,20,21,22]. On the other hand, associations of human milk metabolites were also found with maternal phenotype and diet [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of breast milk is not stable; on the contrary, it undergoes a series of transformations according to the biological age and physiological needs of the infant (5,29,30). It has even been shown that the external environment (geographical location), the internal environment (mode of delivery), the state of mind, and the dietary intake of the mothers can alter the composition of the milk (31)(32) (33).…”
Section: Analysis Of the Documentsmentioning
confidence: 99%
“…The first 1000 days of life (from conception to 2 years of age) are extremely important for the proper development and prevention of diseases in the context of metabolic programming [32]. Metabolomics may be a tool that can help to understand the early health programming of infants from birth [37]. The metabolome of human milk is subject to changes depending on various factors.…”
Section: Introductionmentioning
confidence: 99%